2022
DOI: 10.1002/brb3.2677
|View full text |Cite
|
Sign up to set email alerts
|

Apremilast exerts protective effects on stroke outcomes and blood–brain barrier (BBB) dysfunction through regulating Rho‐associated protein kinase 2 expression

Abstract: Aims: Stroke is a devastating event and a huge public health concern worldwide.Apremilast (APR) is a selective inhibitor of phosphodiesterase-4 involved in various neurological diseases, including stroke. However, the protective effects of APR on stroke have not been investigated. Here, we explored the effects of APR on stroke outcomes and blood-brain barrier (BBB) dysfunction using a middle cerebral artery occlusion (MCAO) stroke mice model. Results:The results show that APR attenuated neurological injury in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Interestingly, apremilast has been recently suggested to have protective effect on cerebral ischemic stroke in a mouse model. 7 Taking together, our data suggest an increased risk of ICS in psoriasis population treated with anti-IL23 antibodies compared to general population, unlike other treatments. However, no specific increased risk is observed with risankizumab as compared to the other anti-IL-23 antibodies.…”
Section: E1448 |mentioning
confidence: 56%
“…Interestingly, apremilast has been recently suggested to have protective effect on cerebral ischemic stroke in a mouse model. 7 Taking together, our data suggest an increased risk of ICS in psoriasis population treated with anti-IL23 antibodies compared to general population, unlike other treatments. However, no specific increased risk is observed with risankizumab as compared to the other anti-IL-23 antibodies.…”
Section: E1448 |mentioning
confidence: 56%
“…Arias de la Rosa et al also observed that treatment with apremilast significantly reduced the levels of CVD-related markers (in particular of CVD-related proteins associated with the pathogenesis of PsA, including FABP-4, GAL-3, MMP3, and CD163), particularly in patients with a higher prevalence of cardiometabolic comorbidities [ 13 ]. Moreover, a recent study on stroke in mice models found a significant efficacy of apremilast on ischemic stroke outcomes by alleviating enhanced blood–brain barrier permeability and neuroinflammation through ROCK2 inhibition, suggesting its potential use as a therapeutic option for ischemic stroke [ 26 ].…”
Section: Discussionmentioning
confidence: 99%